Solid waste landfills in middle and lower-income countries a technical guide to planning, design, and operation (Washington, DC World Bank, 1999)
This technical guide seeks to demonstrate that, by encouraging small, continuous improvements in landfill siting, construction, and operation, the accumulative effect over time is the achievement of better operations. The guide does not seek an immedi ate adoption of sanitary landfill practices. Instead, sanitary landfill is regarded as an eventual goal for which middle- and lower-income countries can plan during the course of several years. A common theme throughout the guide is the emphasis on the practical ways landfills can evolve, as resources and confidence increase, from open dumps to "controlled" dumps to "engineered" landfills and perhaps, one day, to sanitary landfills.
Includes bibliographical references (p. 243-246).
Keywords: Refuse and refuse disposal -- Developing countries; Sanitary landfills -- Design and construction; Sanitary landfills -- Management; Electronic books; TECHNOLOGY & ENGINEERING -- Environmental -- Waste Management; Electronic books